Natural resources management to deliver Sustainable Development Goals (SDGs) - Wahyu Widiyono (Indonesian Journal of Applied Environmental Studies, 2020)
Indonesia is known as a rich natural resources country, but at the same time has a problem of water shortage, soil degradation, pollution, agriculture and forest production, biodiversity conservation, and mineral and energy sustainability. The national natural resources management planning alignment with SDGs programme, particularly the water resources management,  afforestation programme,  a guide for sustainable management of Indonesias biodiversity, government and non-government organizations participant in conservation practice, exploring alternative energy sources to reduce dependence on oil, mainstreaming of SDGs into National Development agenda, National Action Plan, and  SDGs program for Sub-national level. This program was participated by all stakeholders included government, civil society organizations, philanthropy and business society, academics as well as experts. This literature review paper will discuss about the natural resources management to deliver sustainable development goals programme in Indonesian, with specific and focus topics for water and pollution, soil, land product  (agriculture, forest and biological resources), mineral and energy. The objective of this paper was to describe  the alignment of the natural resources management planning and SDGs programme as evaluation to improve their implementation in Indonesia. Though the government has already implemented SDGs program but innovative strategic need to be developed.Indonesia dikenal sebagai negara yang kaya sumberdaya alam, tetapi pada saat yang sama menghadapi masalah kelangkaan air, degradasi lahan, polusi, produksi pertanian dan kehutanan, konservasi keanekaragaman hayati, keberlangsungan mineral dan energi. Rencana pengelolaan sumberdaya alam nasional sejalan dengan program SDGs,  khususnya terkait pengelolaan air, program perhutanian, pengelolaan keanekaragaman hayati secara berkelanjutan, pemerintah dan para pihak yang berpartisipasi dalam praktek konservasi, eksplorasi energi alternatif untuk mengurangi ketergantungan pada minyak bumi, dan pengarus-utamakaan program SDGs ke dalam agenda pembangunan nasional, rencana aksi nasional, dan program di tingkat wilayah. Program ini diikuti oleh seluruh para pihak, termasuk pemerintah, organisasi masyarakat sipil, masyarakat bisnis dan filantropi, kaum akademisi dan para ahli. Studi Pustaka ini akan membahas tentang pengelolaan sumberdaya alam untuk mencapai program pembangunan berkelanjutan di Indonesia, khususnya tentang masalah air, polusi, produsi lahan (meliputi pertanian, hutan, sumberdaya biologi), mineral dan energi. Tujuan penulisan naskah adalah untuk memberikan gambaran keterkaitan antara rencana pengelolaan sumberdaya alam dan pelaksanaan program pembangunan berkelanjutan, sebagai evaluasi untuk meningkatkan implementasinya di Indonesia. Meskipun pemerintah telah melaksanakan program SDGs, tetapi strategi yang inovatif perlu dikembangkan.